Exploring the effectiveness of the Merdeka curriculum in promoting effective learning practices - Lara Prahastina; Mintasih Indriayu; Matsuri Matsuri (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The urgency of this research stems from the need to adapt educational curricula to the evolving demands of post-pandemic learning environments. This study aims to explore the implementation of the Merdeka Curriculum (Curriculum Merdeka Belajar) at SDN Bolo 01, focusing on how teacher practices support the achievement of effective learning. By generating insights into the operationalization of the curriculum and identifying strategies to overcome implementation challenges, this research seeks to provide practical recommendations for elementary schools transitioning to the Merdeka This qualitative case study was conducted at SDN Bolo 01, Madiun Regency, East Java, Indonesia. Data were collected through interviews with school principals, classroom teachers, students, and parents, as well as observations and focus group discussions. The data were analyzed using an inductive model to generate themes and interpret The results indicate that SDN Bolo 01 has made significant efforts to implement innovative, student-centered learning practices aligned with the Merdeka Curriculum, such as Project-Based Learning accommodating the Pancasila Student Profile. However, challenges were identified, including teachers' limited experience and references, students' difficulty concentrating, parents' struggles in assisting learning at home, and classroom management issues in Islamic Religious Education. Efforts to address these challenges include teacher working group activities, independent training, parent mentoring, extra lessons for students, and coordination among Islamic Religious Education teachers. This study provides an in-depth qualitative exploration of the implementation of the Merdeka Curriculum in a specific elementary school context, focusing on how teacher practices support effective learning. By identifying strategies to overcome implementation challenges, this research offers practical insights for schools transitioning to the Merdeka Curriculum.